2010
DOI: 10.1007/s11172-010-0280-3
|View full text |Cite
|
Sign up to set email alerts
|

Azamacrocyclic nickel(II) and copper(II) complexes bearing aryl substituents: synthesis, properties, and crystal structures

Abstract: A synthetic procedure for preparation of new amphiphilic copper(II) and nickel(II) azamacrocyclic complexes bearing aromatic substituents is developed. The nature of substitu ents is shown to exert a negligible influence on spectral and electrochemical characteristics of the prepared compounds. The X ray diffraction analysis of three copper complexes revealed the formation of the dimers of macrocyclic cations associated by noncovalent interactions, nature of which is determined by the structure of the substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The formation of the azonia N3H + group in (I) leads to clear changes in the C-N-C angles compared to the nonprotonated ones. The sum of these angles in the latter case (345-354 ) is much larger than the canonical value for an sp 3hybridized N atom (ca 327 ), thus indicating their partial sp 2 character (Tsymbal et al, 2010;Andriichuk et al, 2019), while in (I) this parameter equals 335 (2) , demonstrating an sp 2 -tosp 3 transformation of the noncoordinated N atom upon protonation.…”
Section: Research Communicationsmentioning
confidence: 85%
See 1 more Smart Citation
“…The formation of the azonia N3H + group in (I) leads to clear changes in the C-N-C angles compared to the nonprotonated ones. The sum of these angles in the latter case (345-354 ) is much larger than the canonical value for an sp 3hybridized N atom (ca 327 ), thus indicating their partial sp 2 character (Tsymbal et al, 2010;Andriichuk et al, 2019), while in (I) this parameter equals 335 (2) , demonstrating an sp 2 -tosp 3 transformation of the noncoordinated N atom upon protonation.…”
Section: Research Communicationsmentioning
confidence: 85%
“…The methylene group of the substituent at the noncoordinated N3 atom in the six-membered chelate ring is oriented equatorially. Such an arrangement of the substituent, in contrast to an axial orientation, is relatively uncommon and only a few examples of such Cu II complexes with aza-and diazacyclam ligands have been described so far (Shin et al, 2010(Shin et al, , 2012Tsymbal et al, 2010;Husain et al, 2012;Xia et al, 2014).…”
Section: Structural Commentarymentioning
confidence: 99%
“…A search of the Cambridge Structural Database (CSD, version 5.39, last update August 2018; Groom et al, 2016) indicated that only three Cu II -perchlorate complexes of azacyclam macrocycles bearing N-alkyl groups decorated with aromatic rings have been reported (Tsymbal et al, 2010). In addition, four related dicopper(II) complexes with a p-xylylene-bridged bis(azacyclam) ligand and terephthalate anion have been described, none of which includes the diaqua Cu II azacyclam cation .…”
Section: Database Surveymentioning
confidence: 99%
“…All chemicals and solvents used in this work were purchased from Sigma-Aldrich and used without further purification. The starting complexes, [Cu(L1)](ClO 4 ) 2 and [Cu(L2)](ClO 4 ) 2 , were prepared by a method reported in the literature (Tsymbal et al, 2010) using benzylamine or 3-picolylamine, respectively, as locking reagents.…”
Section: Synthesis and Crystallizationmentioning
confidence: 99%
“…Hexaazamacrocyclic complexes are of great importance with potential applications in antimicrobial activity [1,[3][4][5][6], photosynthesis [7], catalysis [8][9][10][11], gas sorption [12,13], and molecular magnetism [14][15][16][17][18]. Copper(II) and nickel(II) having received much attention because of their high thermodynamic stability and kinetic inertness can provide the possibility of synthetically convenient chemical modification of macrocyclic ligand using the template synthetic method [19]. Metal template condensation reaction is simple ''one-pot'' reaction and has been generally utilized due to its ease of use, low cost, and high yield.…”
Section: Introductionmentioning
confidence: 99%